Probiotics and gastrointestinal diseases: A promising complementary medicine resource for treatment of gastrointestinal disorders and diseases - Khatereh Anbari; Majid Firouzi; Saber Abbaszadeh (GarVal Editorial Ltda., 2019)
Context: Probiotics are living microorganisms (bacteria or yeasts) whose swallowing in an appropriate number has beneficial effects on host health and improves the host microflora. Different types of digestive diseases are treated by probiotics, including inflammatory gastrointestinal diseases, functional gastrointestinal disorders, irritable bowel syndrome and ulcerative colitis. Aims: To analyze the role of the effect of probiotics on gastrointestinal disorders, especially intestinal illness. Methods: Articles related to "probiotics and digestive disorders and diseases" were searched in citation databases including PubMed, Institute for Scientific Information, Scopus, Google Scholar and Magiran. The search strategy was based on the terms "probiotics and gastrointestinal disorders". Clinical trials and systematic reviews regarding the effects of probiotics on the prevention and treatment of gastrointestinal diseases were included. Irrelevant articles were deleted, and the rest of the articles were used to conduct review. Results: Lactobacillus rhamnosus GG, Bifidobacterium lactys, Streptococcus thermophilus, Saccharomyces boulardii, Escherichia coli Nissle, Probiotic VSL#3, Bacillus coagulants, Lactobacillus acidophilus and Streptococcus thermophilus are one of the most important probiotics that affect gastrointestinal disorders. Conclusions: According to the findings found in this review from clinical trials regarding the effects of probiotics on the prevention and treatment of gastrointestinal diseases, there is evidence that the probiotics have beneficial effects on the gastrointestinal disorders.